Outcomes of Twin Pregnancies in Women 45 Years of Age or Older. Issue 5 (May 2017) - Gerber, Rachel S.; Fields, Jessica C.; Barberio, Andrea L.; Bodenlos, Kimberly; Fox, Nathan S.
Abstract : OBJECTIVE: To investigate outcomes of twin gestations in women 45 years or older at the time of delivery. METHODS: This was a retrospective cohort study of 139 women with twin gestations who were at least 45 years old when they delivered. They were cared for at two referral centers between 2005 and 2016. Analysis included baseline characteristics and pregnancy outcomes including mode of delivery, gestational age at delivery, hypertensive disease in pregnancy, gestational diabetes, and fetal growth restriction. Univariate analysis of the association between patient characteristics and outcomes was performed. RESULTS: The mean maternal age at delivery was 47.3±1.9 years with 99.3% undergoing in vitro fertilization and 95% using donor eggs. Patients had low baseline rates of hypertension (7.2%), obesity (9.5%), and pregestational diabetes (1.4%). The average gestational age of delivery was 35.4 weeks; 22.3% delivered before 34 weeks of gestation. There were high rates of cesarean delivery (93.5%, 95% confidence interval [CI] 87.7–96.8%), preeclampsia (44.6%, 95% CI 36.3–53.3%), and gestational diabetes (19%, 95% CI 13.0–26.8%). Preeclampsia developed in 50.5% of nulliparous women compared with 30.5% of women with a prior birth ( P =.028). Preterm birth at less than 34 weeks of gestation occurred in 18.1% of women of white race compared with 30.3% of women of nonwhite race ( P =.036). CONCLUSION: Twin pregnancy in a predominantly healthy cohort of women who were at least 45 years old when they delivered was associated with high rates of cesarean delivery, preeclampsia, and gestational diabetes, but overall favorable outcomes. Abstract : Twin pregnancy in women aged 45 years or older is associated with high rates of preeclampsia, gestational diabetes, and cesarean delivery, but overall outcomes are favorable.